Clinical Efficacy of HiPorfin Photodynamic Therapy for Advanced Obstructive Esophageal Cancer. (23rd June 2020) - Zeng, Ruifang; Liu, Chen; Li, Libo; Cai, Xiaojun; Chen, Run; Li, Zhiwen
Objective: To explore the clinical efficacy of HiPorfin photodynamic therapy for advanced esophageal cancer and evaluate its impact on survival. Methods: Retrospective analysis of 32 patients with advanced obstructive esophageal cancer at our institution from September 2013 to December 2016. HiPorfin was infused as the photosensitizer at a dose of 5 mg/kg, and after 48 hours, 630-nm laser irradiation was subsequently performed through an optical fiber that passed through the biopsy channel of a flexible endoscope. Results: The effectiveness rate was 78.1% (25/32), and the significant efficacy rate was 56.3% (18/32). The dysphagia score decreased from 3.43 ± 0.73 to 1.79 ± 0.53 ( P < .05). There was no grade 3 or more toxicity. The median overall survival was estimated to be 16 months. Univariate analysis showed higher overall survival with a Karnofsky Performance Status score ≥80 compared with a Karnofsky Performance Status score <80 (hazard ratio: 2.626; 95% CI: 1.091-6.322; P = .024). Overall survival was higher in patients who had received radiation therapy than in patients who did not receive radiation therapy (hazard ratio: 3.574; 95% CI: 1.501-8.510; P = .002). Conclusion: Photodynamic therapy is an effective method for advanced esophageal cancer. The side effects are mild, and the short-term effect is good, especially in the relief of dysphagia. Photodynamic therapy can prolong the survival of patients with advanced esophageal cancer, and the Karnofsky Performance Status score and previous radiation therapy have a significant effect on the overall survival.